Redox response of actinide materials to highly ionizing radiation - Tracy, Cameron L.; Lang, Maik; Pray, John M.; Zhang, Fuxiang; Popov, Dmitry; Park, Changyong; Trautmann, Christina; Bender, Markus; Severin, Daniel; Skuratov, Vladimir A.; Ewing, Rodney C. (Nature communications, 2015)
Energetic radiation can cause dramatic changes in the physical and chemical properties of actinide materials, degrading their performance in fission-based energy systems. As advanced nuclear fuels and wasteforms are developed, fundamental understanding of the processes controlling radiation damage accumulation is necessary. Here we report oxidation state reduction of actinide and analogue elements caused by high-energy, heavy ion irradiation and demonstrate coupling of this redox behaviour with structural modifications. ThO 2 , in which thorium is stable only in a tetravalent state, exhibits damage accumulation processes distinct from those of multivalent cation compounds CeO 2 (Ce 3+ and Ce 4+ ) and UO 3 (U 4+ , U 5+ and U 6+ ). The radiation tolerance of these materials depends on the efficiency of this redox reaction, such that damage can be inhibited by altering grain size and cation valence variability. Thus, the redox behaviour of actinide materials is important for the design of nuclear fuels and the prediction of their performance. Understanding the degradation of materials subject to energetic radiation is important for the development of technologies based on nuclear fission. Here, the authors show that redox reactions of actinide compounds play an important role in their response to energetic radiation and their radiation tolerance.